Effects of the ecological factors on vegetation in river basins of northern part of Mersin city South of Turkey - Duran, Celalettin; Günek, Halil (Ersin YÜCEL, 2010)
In a region, being the certain ratio and coexist of ecological factors which are dominant, determines the ecological conditions of vegetation at that region. Study area is between coastal zone that near the sea side and alpine zone which is the western of Bolkar Mountains. According to the grid square system adopted by Davis in Flora of Turkey, it takes place within the C5 square which has the largest number of endemic plants. Thus there are seen different sort of vegetations inside the study area. The parts where the vegetation becomes dense are generally rugged terrain. With this study, effects on vegetation of climate, geology, topography, soil conditions, hydrographic and anthropogenic impacts were analyzed in the specified basins. Rising behind the city of Mersin mountainous-hilly area is the most important expanding of the vegetation. Mediterranean climate, which is an indicator of the vegetation types and floristic elements, creates the characteristic of climate-vegetation which are adapted to rainy winters and dry summer periods. Humid marine influence, during the vegetation period African-field dust, long-lasting summer drought period, geological structures which affects soil condition, geomorphologic structure which affects climatic parameters are completely affects on growing media of surveyed area. Insufficient soil and water limits the plants life

Bir bölgedeki bitki örtüsünün ekolojik şartlarını, o bölgede egemen olan ekolojik faktörlerin belirli oranda ve bir arada bulunması belirler. İnceleme alanı, deniz seviyesini oluşturan kıyı kuşağı ile Bolkar Dağlarının batısını oluşturan alpin kuşak arasındadır. Davis’in kareleme sistemine göre endemik bitki sayısının en fazla olduğu C5 karesi içinde yer alır. Nitekim çalışma sahasında farklı tipte vejetasyon örtüsü görülür. Bitki örtüsünün yoğunlaştığı bölümler, genellikle Karst topografyasının arızalı kesimleridir. Bu çalışma ile belirlenen akarsu havzalardaki iklim, jeolojik yapı, topografya, toprak şartları, hidrografik ve antropojenik faktörlerin bitki örtüsü üzerine etkileri incelenmiştir. Mersin kenti gerisinde yükselen dağlık-tepelik arazi, bitki örtüsünün en önemli yayılış alanıdır. Akdeniz ikliminin göstergesi olan vejetasyon tipleri ve floristik elemanlar, yağışlı kış ve kurak yaz dönemlerine uyum sağlamış karakteristik iklim-bitki örtüsünü oluşturur. Akdeniz’in denizel nemli etkisi, vejetasyon periyodu boyunca Afrika kökenli Sahra tozları, uzun süren yaz kuraklık periyodu, toprak şartlarını etkileyen jeolojik yapı, lokal iklimsel parametreleri etkileyen topografik yapı gibi unsurlar, incelenen sahadaki bitki örtüsünün yetişme ortamı verimliliği üzerinde etkilidir. Toprak ve su kıtlığı, bitki yaşamını sınırlandırır
Mersin kenti kuzeyi akarsu havzalarındaki ekolojik faktörlerin bitki örtüsüne etkisi